Penggunaan Bajakah Tengang Dalam Upacara Hindu Kaharingan - Sri Kayun; Ni Wayan Eka Sumartini; Apri Apri (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Hindu Kaharingan communities in the region of Central Kalimantan, particularly in Kasongan Regency, have religious rituals in accordance with their religious teachings. The implementation of religious rituals by the Hindu Kaharingan community in Kasongan Regency, Central Kalimantan, utilizes various ceremonial tools obtained from the Kalimantan environment. One of the tools used in several Hindu Kaharingan religious rituals is the Bajakah Tengang. This research aims to identify the types of ceremonies that utilize the Bajakah Tengang as a ceremonial tool and the method of using the Bajakah Tengang in specific ceremonies/rituals. The research findings indicate that the types of ceremonies using the Bajakah Tengang include marriage ceremonies, manenung, mambayar hajad, tiwah, and nyadiri. The Bajakah Tengang is used by being tied to the right hand and should not be removed until the Bajakah Tengang falls off on its own.